MANAJEMEN PEMBELAJARAN DI MADRASAH DAN PESANTREN - Zaedun Na'im; Addin Kholisin (STAI Ma'had Aly Al-Hikam Malang, 2022)
Learning is an important concern in achieving a success obtained by students from the impact of educational activities in an educational institution whose indicators can be seen from the effectiveness of learning carried out by educators and therefore proper management is needed from an educator, so that the name management mastery is needed. learning. This research method uses a qualitative approach with the type of library research by searching for literature that discusses learning management in Islamic boarding schools and madrasas, then an analysis is carried out to obtain findings and conclusions. The result of this research is that learning in Islamic boarding schools and madrasas has its own characteristics, namely the usual learning methods in Islamic boarding schools, namely wetonan, sorogan, bandongan, and memorization. And if it is associated with learning management, of course, not all of them are applied by pesantren, such as the existence of lesson plans, syllabi, and others, considering that learning in pesantren refers to the book being studied, so the target achievement is to complete the contents of the book, then if it is associated with learning evaluation it does not as in the case of madrasas applying semester exams as a condition for grade promotion, but in pesantren applying memorization of a nadhom which is a requirement for grade promotion, such as nadhom imriti, alfiyah, and othersKeywords: learning management, madrasah, pesantren